Pain management in primary care – current perspectives - H.P. Meyer (South African Family Practice)
According to a 1998 World Health Organization Survey of 26 000 primary care patients on five continents, 22% reported persistent pain over the past year. Part of the problem lies with some health-care providers who have failed to keep up with the advances in pain medicine and continue to follow the biomedical approach, which regards a specific pathway as the only source of pain. In this model, all pain is regarded as a warning signal of tissue injury, and if conservative treatment fails, some surgical technique will be able to correct the problem. The modern paradigm of pain management has moved from this biomedical to the broader biopsychosocial approach, where pain mechanisms now integrate input from sensory, emotional and cognitive systems.